Pengembangan Mobile Learning Berbasis Client Server Pada Mata Pelajaran Simulasi Digital - Jhon Veri; Rini Sefriani; Leo Aulia (Jurnal KomtekInfo, 2018)
This study aims to determine the level of Validity, Practicality and Effectiveness of Client Server-based Mobile Learning media in SMK Negeri 9 Padang. Because there are still limited learning resources and learning media in the form of interactive multimedia with mobile learning packaging at Padang Vocational High School 9. The study uses a development model (Four-D model). The development steps are (1) Define, (2) Design, (3) Development, and (4) Disseminate. The trial instrument was conducted on 31 students at Padang N 9 Vocational School. The sample in this study was 31 students. The results showed that the level of validity obtained was 82.17% with valid interpretations, the practicality level was 82.29%, which meant that it was practically used and for the effectiveness test level of 90.03, which meant that it was very effective to use the Learning Media Client Server Based Learning Media. Digital Simulation at SMKN 9 Padang